Effects of different sowing dates on biomass allocation of various organs and allometric growth of Fagopyrum esculentum - Wang, Heqi; Wang, Congwen; Fan, Gaohua; Fu, Changxing; Huang, Yingxin; Liu, Xuhe; Wang, Shirui; Wang, Kunling (Frontiers in Plant Science, 2024)
Introduction The sowing date plays a crucial role in influencing the growth and reproduction of plants, with its specific impact on biomass allocation and allometric growth remaining unclear. Understanding these effects is essential for optimizing agricultural practices and enhancing crop productivity. Methods To investigate the effects of sowing dates on biomass allocation and allometric growth, a field experiment was conducted with sequential sowings of Fagopyrum esculentum from April 12th to August 11th in 2018. Biomass measurements were taken across various plant organs, and corresponding allocation calculations were made. A detailed analysis of the allometric growth relationship involving organ biomass variations was performed. Results The study revealed that the accumulation and allocation of organ biomass in buckwheat were significantly impacted by the sowing dates. Delayed planting led to reduced vegetative growth and increased biomass allocation towards reproduction. Allometric parameters such as exponent, constant, and individual size of buckwheat were notably affected by delayed planting. Interestingly, the allometric exponents governing the relationships between reproductive vs. vegetative biomass and belowground vs. aboveground biomass exhibited varying trends across different sowing dates. Discussion Notably, late sowings resulted in significantly higher reproductive biomass compared to early and middle sowings. These findings highlight the nuanced relationship between plant size and reproductive biomass under different sowing dates, emphasizing the critical role of planting timing in shaping mature plant sizes and reproductive outcomes. The study underscores the importance of considering sowing dates in agricultural practices to optimize plant growth and productivity.